Mesenchymal Stem Cells Mitigate Cirrhosis through BMP7 - Bing Li; Qing Shao; Dong Ji; Fan Li; Guofeng Chen (Cellular Physiology and Biochemistry, 2015)
Background/Aims: Transplantation of mesenchymal stem cells (MSCs) has therapeutic effects on various diseases, while its effect on developing cirrhosis as well as the underlying mechanism remained largely unknown. Methods: Twenty C57BL/6 mice were randomly separated into 2 groups of ten each. One group received transplantation of MSCs, while the other group received saline as control. The mice then received intraperitoneal injection of carbon tetrachloride (CCl4) twice per week for 8 weeks to develop cirrhosis. After another 4 weeks, the levels of cirrhosis in these mice were evaluated by liver fibrosis area, portal pressure, sodium balance and excretion. Transcripts of transforming growth factor β 1 (TGFβ1) and bone morphogenic protein 7 (BMP7) in the mouse livers were quantified by RT-qPCR. BMP7-depleted MSCs were prepared and applied in this model, and compared to MSCs. Results: Liver fibrosis, portal hypertension and sodium retention that were developed by CCl4, were all significantly alleviated by MSCs transplantation, which decreased TGFβ1 levels and increased BMP7 levels in the injured liver. MSCs were found to express extremely high levels of BMP7. Knockdown of BMP7 in MSCs completely abolished the protective effect of MSCs against CCl4-induced cirrhosis. Conclusions: MSCs mitigate cirrhosis through their production of BMP7 against the fibrogenic effect of TGFβ1 in the injured liver.